Video End. (Graz : Pool pfirisch, 1976)
Vostell, Wolf ; Bloch, Peter ; Howkins, John ; Davis, Douglas ; Dennis, John ; Druks, Michael ; Fansten, Michel ; Haberl, Horst G. ; Herzogenrath, Wulf ; Kriesche, Richard ; Pezold, Friederike ; Ross, David A. ; Santanera, Mia ; Tirfoin, Boris
Video End, POOL pfirisch, Graz, 16-17-18 juli 1976
boek